Temel sağlık hizmetlerinde aile merkezli sistemik psikososyal yaklaşım I: Toplumsal süreçler ve riskler - (:unkn) unknown (My University, 2007)
Toplumsal dönüşümler birey, aile ve benzeri birliktelikleri farklı biçimlerde etkilemektedir. Bu etkinin görünür sonuçlarının büyük bir bölümü ruh sağlığı alanında gözlenmektedir. Son yıllarda ruh sağlığı düzeyindeki bu sorun alanları, temel sağlık hizmetlerine başvurunun merkezi konumuna gelmiştir. Temel sağlık hizmetlerinde ruh sağlığını koruyucu modellerin planlanması sırasında temel gereksinmelerden biri de ruh sağlığına yönelik olası yatkınlık kulvarının belirleyicileri olan farklı sosyal süreçlerin belirlenmesi ve bu süreçleri hedef alan modellerin oluşturulmasıdır. Bu yazıda, vaka deneyimleri ışığında 2002-2004 yılları arasında İstanbul Anadolu yakasında temel sağlık hizmetlerinde yürüttüğümüz aile merkezli psikososyal çalışma uygulamamız sırasında gözlenen risk dağarcıkları gözden geçirilecektir. Bu çalışma sırasında aile içi ilişkilerde öne çıkan risk alanları izolasyon ve ayrışma, sosyal kesinti ve devamsızlık, baskın söylem yaşantısı başlıkları altında ele alınacaktır.

Social changes have an important impact on individual, family and community agendas. The consequences of this impact are particulary strong with in mental health context. Especially in countries which go through an economic and political transition such an impact becomes more visible within the public service sector. In recent years primary health care setting became the central point of referral for these problems in Turkey as well. Especially general practitioners and family physicians took a new role as social agents in their daily routine. Despite this growing need within the primary care setting, the link between mental health services and primary care health workers are limited and much needed psychosocial approaches are missing on the ground. Most of the existing tools seem to concentrate on symptom based view of psychiatric practice. However wider approaches which will contain the psychosocial need of the referrals are needed. Currently, one of the main targets of community based psychosocial interventions is to determine the contextual factors that might contribute to overall vulnerability in the community. In this paper, vulnerability and risks factors which were observed during our family based psychosocial interventions in a primary care setting in Istanbul during 2002-2004 will be presented. During the interviews with the families three social agendas dominated the content of the referrals. These agendas will be discussed under isolation- detachment, social discontinuity and dominant discourse experience headings. The social processes and their everyday consequences within these main themes will be covered in the light of family sessions.
Family centered psychosocial systemic approach in primary health care setting I: Social agendas and atteched risks
Keywords: Sağlık Bilimleri ve Hizmetleri; Temel Sağlık Hizmetleri; Psikiyatri